BALANCE EXERCISE TO POSTURAL BALANCE IN ELDERLY AT PTSW KASIH SAYANG IBU, BATUSANGKAR - Wenny Lazdia; Sherly Amelia; Silviani Silviani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. Elderly are the age group most at risk of impaired postural balance due to declining elderly or morphological changes in the muscles that cause functional changes in muscle strength and decreasing muscle contraction. Decreasing in postural balance due to decreased muscle strength can be improved by doing exercises that are useful to keep the muscle function and posture remains well one of them is balance exercise. The purpose of this study was to analyze influence of balance exercise to postural balance on elderly in PTSW Kasih Sayang Ibu Batusangkar. Methods. This research used a pre - experimental design one group pre - post test design with One Group Pre - Post Test Design. Population and sample of the study was elderly with impaired postural balance that met the inclusion criteria by using were purposive sampling techniques they were 41 respondents. This study was conducted from July to September 2013 in PSTW Kasih sayang Ibu Batusangkar. Measuring instruments used in this study is a questionnaire for the elderly demographic data and tools to measure the level of the elderly postural balance sheet observation Berg Balance Scale. Results. While the results obtained from the significant influence of postural balance elderly before and after exercise balance with p value 0.000 with a mean difference of 8,171. Discussion. Elderly with postural balance disruption suggest to do balance exercise to keep dynamic and static stability, so can increase quality of life. Keywords: Balance Exercise, Postural Balance, Elderly